PENGARUH SPIRITUALITAS KERJA TERHADAP MOTIVASI KERJA: STUDI KASUS PADA U-PRO CHAPTER KUPANG, FULL GOSPEL BUSINESSMEN’S FELLOWSHIP INTERNATIONAL (FGBMFI) KUPANG - Samuel Messakh; Rolland E. Fanggidae; Ronald P.C. Fanggidae (Journal of Management Small and Medium Enterprises (SMEs), 2018)
This research executed in U-Pro Chapter Kupang, Full Gospel Businessmen’s FellowshipInternational (FGBMFI) Kupang with the total sample of 36 people. The result of the studysuggested that (1) Work Spitituality and Motivation in U-Pro Chapter Kupang are in acriterion of very high and very high. (2) Work Spirituality has positive influencesignificantly to Work Motivation at U-Pro Chapter Kupang. This could be seen in formula ofSimple Regression : Y = 14,30 + 0,906X. The the result proved that Work Spirituality had apositive impact significantly on Work Motivation by 0.67 or 67 %, the rest 33 % influenced byother factors.Keywords : Work Spirituality, Work Motivation